Stability of Triangular Equilibrium Points in the Generalised Photogravitational Restricted Three Body Problem (International Journal of Scientific Research in Science and Technology, 2026)
This paper investigates the stability of triangular equilibrium points (L4, L5) in the generalized photogravitational restricted three‑body problem, considering the combined effects of radiation pressure and oblateness of both primaries. Using variational equations and characteristic roots, the linear stability conditions are derived. The analysis shows that triangular points are stable when the mass parameter lies within 0   < c, and unstable otherwise. The critical mass ratio c is obtained, and its range of stability is shown to increase, decrease, or remain unchanged depending on the sign of parameter p, which depends on radiation and oblateness coefficients. These results demonstrate that oblateness and radiation significantly modify the location and stability of triangular points compared to the classical restricted three‑body case, offering deeper insights into celestial mechanics and artificial satellite dynamics